Clinical and genetic characteristics of BAP1-mutated non-uveal and uveal melanoma - Matull, Johanna; Placke, Jan-Malte; Lodde, Georg; Zaremba, Anne; Utikal, Jochen; Terheyden, Patrick; Pföhler, Claudia; Herbst, Rudolf; Kreuter, Alexander; Welzel, Julia; Kretz, Julia; Möller, Inga; et al. (Frontiers in Immunology, 2024)
Background: Screening for gene mutations has become routine clinical practice across numerous tumor entities, including melanoma. BAP1 gene mutations have been identified in various tumor types and acknowledged as a critical event in metastatic uveal melanoma, but their role in non-uveal melanoma remains inadequately characterized.Methods: A retrospective analysis of all melanomas sequenced in our department from 2014-2022 (n=2650) was conducted to identify BAP1 mutated samples.Assessment of clinical and genetic characteristics was performed as well as correlations with treatment outcome.Results: BAP1 mutations were identified in 129 cases and distributed across the entire gene without any apparent hot spots. Inactivating BAP1 mutations were more prevalent in uveal (55%) compared to non-uveal (17%) melanomas. Non-uveal BAP1 mutated melanomas frequently exhibited UV-signature mutations and had a significantly higher mutation load than uveal melanomas. GNAQ and GNA11 mutations were common in uveal melanomas, while MAP-Kinase mutations were frequent in nonuveal melanomas with NF1, BRAF V600 and NRAS Q61 mutations occurring in decreasing frequency, consistent with a strong UV association. Survival outcomes did not differ among non-uveal melanoma patients based on whether they received targeted or immune checkpoint therapy, or if their tumors harbored inactivating BAP1 mutations.In contrast to uveal melanomas, where BAP1 mutations serve as a significant prognostic indicator of an unfavorable outcome, BAP1 mutations in nonuveal melanomas are primarily considered passenger mutations and do not appear to be relevant from a prognostic or therapeutic perspective.